One week to claim it all - Herrera, Adriana (Romance author) (Harlequin desire, 2021)
"She's on track to be the new CEO. Her ex is the only one standing in the way. When Esmeralda Sambrano-Peña unexpectedly inherits her father's media empire, it ruffles more than a few feathers. And no one is more conflicted about it than Rodrigo Almanzar. Esmeralda knows her father's longtime protégé--and her ex-lover--wants the executive job for himself. Making matters worse, their renewed passion grows undeniable with every late-night meeting. Will Rodrigo prove to be the perfect partner in business and pleasure--or her professional undoing?"--Back cover.